2016
DOI: 10.1016/j.neuropharm.2016.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Acute mechanical sensitization of peripheral nociceptors by aldosterone through non-genomic activation of membrane bound mineralocorticoid receptors in naive rats

Abstract: Recently, there is increasing interest in the role of peripheral mineralocorticoid receptors (MR) to modulate pain, but their localization in neurons and glia of the periphery and their distinct involvement in pain control remains elusive. In naive Wistar rats our double immunofluorescence confocal microscopy of the spinal cord, dorsal root ganglia, sciatic nerve and innervated skin revealed that MR predominantly colocalized with calcitonin-gene-related peptide (CGRP)- and trkA-immunoreactive (IR) nociceptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…Finally, the tissues were washed in PBS, and nuclei were stained with DAPI (4′,6-diamidino-2-phenylindole) and then mounted in Vectashield (Vector Laboratories) and imaged on a confocal laser scanning microscope, LSM510, as described previously [19]. Then, the photographs were taken by a confocal microscope (633 nm; Carl Zeiss, Göttingen, Germany) as described in our previous study [20]. To demonstrate specificity of staining, the following controls were included: omission of the primary antisera or the secondary antibodies, as described in our previous studies [19].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the tissues were washed in PBS, and nuclei were stained with DAPI (4′,6-diamidino-2-phenylindole) and then mounted in Vectashield (Vector Laboratories) and imaged on a confocal laser scanning microscope, LSM510, as described previously [19]. Then, the photographs were taken by a confocal microscope (633 nm; Carl Zeiss, Göttingen, Germany) as described in our previous study [20]. To demonstrate specificity of staining, the following controls were included: omission of the primary antisera or the secondary antibodies, as described in our previous studies [19].…”
Section: Methodsmentioning
confidence: 99%
“…2,15 More recently, we identified mineralocorticoid receptors predominantly on the subpopulation of peptidergic unmyelinated nociceptive C-fibers, strongly indicating a role for the modulation of nociception. 16 Indeed, local application of the mineralocorticoid receptor agonist aldosterone at the peripheral and central nerve terminals of nociceptive neurons elicited a rapid increased mechanical sensitivity. 16 Consistent with this pronociceptive effect, previous studies have shown that aldosterone increased the number of action potentials that were evoked in acutely dissociated dorsal root ganglion neurons.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 99%
“…16 Indeed, local application of the mineralocorticoid receptor agonist aldosterone at the peripheral and central nerve terminals of nociceptive neurons elicited a rapid increased mechanical sensitivity. 16 Consistent with this pronociceptive effect, previous studies have shown that aldosterone increased the number of action potentials that were evoked in acutely dissociated dorsal root ganglion neurons. 2,15,17 These effects occurred rapidly, were most likely due to nongenomic mechanisms, and were mediated by membrane-bound mineralocorticoid receptors which were identified by membrane saturation binding.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 99%
See 2 more Smart Citations